2021
DOI: 10.1177/2333794x211035258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Lactose Formula on the Short-Term Outcomes of Neonatal Abstinence Syndrome: A Systematic Review

Abstract: The use of low lactose formula (LLF) in term and near-term infants in infants with neonatal abstinence syndrome (NAS) has been increasing recently. However, the clinical evidence of such use is limited. Our aim in this paper was to systematically review the current literature about the use of LLF in infants with NAS. We searched PubMed, Embase, Cumulative Index to Nursing and Allied Health Literature, and Cochrane Database of Systematic Reviews for articles published between 2015 and 2020. Only randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…70 In some NICUs, lactosereduced formulas are selected for enteral feeding of infants with neonatal abstinence syndrome when human milk is not available, but evidence to support this practice is lacking. [71][72][73][74] Congenital lactase deficiency is a rare disorder; however, it is an indication for the use of lactose-free formula as the condition might be associated with lifethreatening dehydration and electrolyte abnormalities. 75…”
Section: Soy Formulasmentioning
confidence: 99%
See 1 more Smart Citation
“…70 In some NICUs, lactosereduced formulas are selected for enteral feeding of infants with neonatal abstinence syndrome when human milk is not available, but evidence to support this practice is lacking. [71][72][73][74] Congenital lactase deficiency is a rare disorder; however, it is an indication for the use of lactose-free formula as the condition might be associated with lifethreatening dehydration and electrolyte abnormalities. 75…”
Section: Soy Formulasmentioning
confidence: 99%
“…However, a randomized controlled trial found no difference in the incidence of fussiness, cramping, spitting up, colic, gas, and sleeplessness in healthy term infants receiving a lactose‐free formula vs lactose‐containing formula 70 . In some NICUs, lactose‐reduced formulas are selected for enteral feeding of infants with neonatal abstinence syndrome when human milk is not available, but evidence to support this practice is lacking 71–74 . Congenital lactase deficiency is a rare disorder; however, it is an indication for the use of lactose‐free formula as the condition might be associated with life‐threatening dehydration and electrolyte abnormalities 75 …”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that the high-caloric formulas were associated with less treatment failure, less weight loss, and shorter LOS compared to lower caloric formula ( 51 ). Although low-lactose formulas are perceived to alleviate gastrointestinal issues during the withdrawal period ( 51 ), several studies showed that low-lactose formula did not improve NAS outcomes ( 30 , 52 , 53 ).…”
Section: Ongoing Management and Long-term Effects Of Nasmentioning
confidence: 99%